The Gender Gap in Private Pensions - Bardasi, Elena; Jenkins, Stephen P. (2012)
In many western countries, older women receive considerably less private pension income than older men on average. We analyse this differential in Britain, examining differences between the sexes both in private pension coverage and in pension income conditional on receipt. Using regression-based decompositions, we show that both gender gaps are associated mainly with differences in returns to personal characteristics rather than with differences in personal characteristics per se.